Method for manufacturing a recycled cathode active material

CN123023170APending Publication Date: 2026-10-30SUMITOMO CHEM CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580022549.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-28
Filing Date
2025-03-06
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0019]根据本公开,能够提供能够使使用再循环正极活性物质制造的电池的倍率特性与使用未使用过的正极活性物质制造的电池的倍率特性进一步为相同程度的再循环正极活性物质的制造方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

A method for producing a recycled positive electrode active material includes the following steps. (1) A step of mixing a positive electrode mixture including a positive electrode active material and an activation treatment agent containing one or two or more alkali metal compounds to obtain a mixture (2) A step of heating the mixture at a temperature T °C to obtain a heated mixture (3) A step of heating the heated mixture at a temperature (1.6 x T) °C or higher to recover a heated positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to a method for manufacturing a recyclable positive electrode active material. Background Technology

[0002] The positive electrode active material of batteries contains rare metals such as cobalt, nickel, manganese, and lithium. In particular, the positive electrode active material of non-aqueous electrolyte secondary batteries utilizes compounds with these rare metals as the main components. In order to conserve the resources of rare metals, methods for reprocessing rare metals from battery waste from secondary batteries are needed.

[0003] For example, Patent Document 1 discloses a method in which a positive electrode binder is mixed with an activating agent containing an alkali metal compound, the mixture is heated to decompose the binder, and the decomposed products and activating agent are removed using water or the like to recover the positive electrode active material. This method is cost-effective in that it recovers the positive electrode active material directly from battery waste without using organic solvents.

[0004] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2012-186150 Summary of the Invention

[0005] The problem that the invention aims to solve

[0006] When recycling the positive electrode active material, there is room for further improvement in the rate characteristics of batteries manufactured using recycled positive electrode active materials.

[0007] Therefore, the object of this disclosure is to provide a method for manufacturing a recycled positive electrode active material that enables the rate characteristics of a battery manufactured using recycled positive electrode active material to be of the same degree as those of a battery manufactured using unused positive electrode active material.

[0008] means for solving problems

[0009] This disclosure includes, for example, the following [1] to [8].

[0010] [1] A method for manufacturing a recyclable positive electrode active material, comprising the following steps. (1) The process of mixing a positive electrode agent containing a positive electrode active material with an activating agent containing one or more alkali metal compounds to obtain a mixture. (2) The process of heating the mixture at a temperature T℃ to obtain the heated mixture. (3) The process of heating the heated mixture at a temperature above (1.6×T)℃ and recovering the heated positive electrode active material.

[0011] [2] A method for manufacturing a recyclable positive electrode active material, comprising the following steps. (1) The process of mixing a positive electrode agent containing a positive electrode active material with an activating agent containing one or more alkali metal compounds to obtain a mixture. (2) The process of heating the mixture at a temperature T℃ to obtain the heated mixture. (3) The process of heating the heated mixture at a temperature above (T+300)℃ to recover the heated positive electrode active material.

[0012] [3] According to the manufacturing method described in [1], wherein the step (3) includes: (3a) The step of contacting the heated mixture with a liquid containing water to obtain a slurry containing a solid component and a liquid component, and then separating the slurry into the solid component and the liquid component; and (3c) A process of recovering the heated positive electrode active material by heating the solid component at a temperature of (1.6×T) °C or higher.

[0013] [4] According to the manufacturing method described in [2], wherein the step (3) includes: (3a) The step of contacting the heated mixture with a liquid containing water to obtain a slurry containing a solid component and a liquid component, and then separating the slurry into the solid component and the liquid component; and (3c) A process of recovering the heated positive electrode active material by heating the solid component at a temperature above (T+300) °C.

[0014] [5] The manufacturing method according to any one of [1] to [4], wherein, in the step (2), the temperature T is lower than the melting start temperature of the activating agent.

[0015] [6] The manufacturing method according to any one of [1] to [5], wherein the positive electrode active material comprises a lithium compound.

[0016] [7] The manufacturing method according to any one of [1] to [6], wherein the positive electrode active material comprises a composite oxide containing at least one element selected from the following group 1 and at least one element selected from the following group 2. Group 1: Ni, Co, Mn, Fe, Al, and P Group 2: Li, Na, K, Ca, Sr, Ba, and Mg

[0017] [8] The manufacturing method according to any one of [1] to [7], wherein the activating agent comprises at least one compound selected from potassium compounds and sodium compounds.

[0018] Invention Effects

[0019] According to this disclosure, a method for manufacturing recycled positive electrode active materials can be provided that enables the rate characteristics of batteries manufactured using recycled positive electrode active materials to be further improved to the same extent as those of batteries manufactured using unused positive electrode active materials. Detailed Implementation

[0020] (Method for manufacturing recycled positive electrode active material)

[0021] The following describes the manufacturing method of the positive electrode active material involved in recycling.

[0022] The method for manufacturing a recyclable positive electrode active material according to one embodiment of the present disclosure includes the following steps. Step (1): A process of mixing a positive electrode agent containing a positive electrode active material with an activating agent containing one or more alkali metal compounds to obtain a mixture. Step (2): Heating the mixture at temperature T℃ to obtain the heated mixture. Step (3): Heating the heated mixture at a temperature above (1.6×T)℃ to recover the heated positive electrode active material.

[0023] In one embodiment of the method for manufacturing recyclable positive electrode active material, a mixture of a positive electrode agent and an activating agent is heated, and then the heated mixture is heated at a temperature slightly higher than the temperature at which the mixture of the positive electrode agent and the activating agent was heated, thereby recovering the heated positive electrode active material. The inventors conducted research and found that by heating the heated mixture at a temperature slightly higher than the temperature at which the mixture of the positive electrode agent and the activating agent was heated, the rate performance of a battery manufactured using recyclable positive electrode active material can be made to be even more similar to that of a battery manufactured using unused positive electrode active material. The inventors speculate that the reason for this is as follows: by heating the mixture of the positive electrode agent and the activating agent and then heating the heated mixture at a temperature slightly higher than the temperature at which the mixture of the positive electrode agent and the activating agent was heated, the crystallite size of the positive electrode active material can be sufficiently increased, thereby improving the rate performance. However, the mechanism of this disclosure is not limited to the above.

[0024] The following is a detailed description of each process.

[0025] Previous process (A): Preparation of positive electrode mixture

[0026] First, a positive electrode mixture containing a positive electrode active material is prepared.

[0027] [Positive Electrode Active Material]

[0028] Examples of the positive electrode active material include composite compounds containing one or two or more of lithium, oxygen, fluorine, sodium, magnesium, aluminum, silicon, phosphorus, sulfur, potassium, calcium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, yttrium, niobium, molybdenum, silver, indium, tungsten and the like as constituent elements. The positive electrode active material may include a lithium compound.

[0029] The positive electrode active material may consist of only a single compound, or may be composed of a plurality of compounds.

[0030] The positive electrode active material preferably contains a composite oxide comprising at least one element selected from the following element group 1 and at least one element selected from the following element group 2. Element group 1: Ni, Co, Mn, Fe, Al and P Element group 2: Li, Na, K, Ca, Sr, Ba and Mg

[0031] The positive electrode active material preferably contains a compound represented by the following formula (A). Li 1+a M 2 b M 1 M T c O 2+d X e (A) wherein, M 2 represents at least one element selected from Na, K, Ca, Sr, Ba and Mg, M 1 represents at least one element selected from Ni, Co, Mn, Fe, Al and P, M T represents at least one element selected from transition metal elements other than Ni, Co, Mn and Fe, X represents at least one element selected from non-metallic elements other than O and P, -0.4<a<1.5, 0≤b<0.5, 0≤c<0.5, -0.5<d<1.5 and 0≤e<0.5 are satisfied.

[0032] M TPreferably, it is selected from at least one element chosen from Cu, Ti, Mg, Al, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, Ca, Sr, Ba, Ge, Cr, Sc, Y, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, and In. Examples of X include F, S, Cl, Br, I, Se, Te, and N.

[0033] The positive electrode active material preferably contains a composite oxide containing at least Li and Ni.

[0034] In the positive electrode active material, M 1 The preferred mole fraction of Ni in the sample is 0.3 to 0.95.

[0035] There are no particular restrictions on the crystal structure of the positive electrode active material (e.g., composite oxide), but a layered structure is preferred, and a hexagonal or monoclinic crystal structure is even more preferred.

[0036] The hexagonal crystal structure belongs to the group selected from P3, P31, P32, R3, P-3, R-3, P312, P321, P3112, P3121, P3212, P3221, R32, P3m1, P31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P61, P65. Any one of the following space groups: P62, P64, P63, P-6, P6 / m, P63 / m, P622, P6122, P6522, P6222, P6422, P6322, P6mm, P6cc, P63cm, P63mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mmm, P6 / mcc, P63 / mcm, and P63 / mmc.

[0037] The crystal structure of the monoclinic form belongs to any one of the space groups selected from P2, P21, C2, Pm, Pc, Cm, Cc, P2 / m, P21 / m, C2 / m, P2 / c, P21 / c, and C2 / c.

[0038] The crystal structure of the positive electrode active material preferably belongs to the space group R-3m in the hexagonal crystal structure or the C2 / m in the monoclinic crystal structure.

[0039] The crystal structure of the positive electrode active material can be identified by the powder X-ray diffraction pattern obtained by powder X-ray diffraction using CuKα rays as the radiation source.

[0040] There are no particular limitations on the particle size of the positive electrode active material in the positive electrode mixture; it can range from 0.001 to 100 μm. The particle size distribution of the positive electrode active material can be determined using a laser diffraction scattering particle size distribution measuring device (e.g., Malvern Mastersizer 2000). A cumulative particle size distribution curve based on the particle size distribution is constructed, and the particle size at 50% accumulation from the microparticle side (D50) can be taken as the average particle size of the positive electrode active material.

[0041] There are no particular restrictions on the content of positive electrode active material in the positive electrode mixture.

[0042] [Adhesive]

[0043] The positive electrode mixture may contain a binder. When the positive electrode mixture contains a binder, the particles of the positive electrode active material can be bonded together by the binder.

[0044] Examples of binders (binders before activation treatment) contained in positive electrode binders include thermoplastic resins, specifically fluoropolymers such as polyvinylidene fluoride (hereinafter sometimes referred to as "PVdF"), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers, hexafluoropropylene-vinylidene fluoride copolymers, and tetrafluoroethylene-perfluorovinyl ether copolymers; polyolefin resins such as polyethylene and polypropylene; and styrene-butadiene copolymers (SBR). A single binder can be used, or two or more can be used in combination.

[0045] There is no particular limitation on the content of the binder in the positive electrode mixture, but it can be within the following ranges relative to 100 parts by weight of the positive electrode active material: The binder content can be 0.5 parts by weight or more, 1 part by weight or more, or 2 parts by weight or more. The binder content can be 30 parts by weight or less, 10 parts by weight or less, or 5 parts by weight or less. From these perspectives, the binder content can be 0.5 to 30 parts by weight, 1 to 10 parts by weight, 1 to 5 parts by weight, or 2 to 5 parts by weight.

[0046] [Conductive Materials]

[0047] The positive electrode binder may contain conductive materials and / or electrolytes. In cases where the positive electrode binder contains binders and conductive materials, the particles of the positive electrode active material and the conductive materials can be bonded together by the binder. The positive electrode binder may contain fluorine compounds from the binder and / or the electrolyte (e.g., the electrolyte in the electrolyte).

[0048] Examples of conductive materials include metallic conductive materials such as metal particles, and carbon-based conductive materials composed of carbon materials.

[0049] Specific examples of carbon-based conductive materials include graphite powder (graphite), carbon black (e.g., acetylene black), and fibrous carbon materials (e.g., graphitized carbon fibers and carbon nanotubes).

[0050] Carbon-based conductive materials can be a single carbon material or composed of multiple carbon materials.

[0051] The specific surface area of ​​carbon materials used as carbon-based conductive materials can range from 0.1 to 500 m². 2 / g. In this case, the conductive material can consist solely of a specific surface area of ​​30m². 2 Composed of carbon-based conductive materials with a specific surface area of ​​30m² or more. 2 Carbon black with a density of 1 g or higher, or a specific surface area of ​​30 m², can also be used. 2 Acetylene black of / g or higher. When using activating agents containing alkali metal compounds with oxidizing power (described later), it is sometimes possible to increase the rate of oxidation treatment of carbon-based conductive materials, even carbon materials with small specific surface areas.

[0052] There are no particular restrictions on the content of conductive material in the positive electrode mixture, but it can be within the following ranges relative to 100 parts by mass of the positive electrode active material: The content of conductive material can be 0 parts by mass or more, more than 0 parts by mass and 1 part by mass, more than 3 parts by mass, or more than 5 parts by mass. The content of conductive material can be 50 parts by mass or less, 40 parts by mass or less, 30 parts by mass or less, 20 parts by mass or less, or 10 parts by mass or less. Based on these points, the content of conductive material can be 0-50 parts by mass, more than 0 parts by mass and 40 parts by mass or less, 1-30 parts by mass, 1-10 parts by mass, 3-20 parts by mass, or 5-10 parts by mass.

[0053] [Electrolytes and Solvents]

[0054] Electrolytes are components derived from the battery's electrolyte and permeated into the positive electrode mixture. Examples of electrolytes include LiPF6, LiBF4, LiClO4, LiN(SO2CF3)2, LiN(SO2F)2, and LiCF3SO3. There are no particular restrictions on the content of electrolytes in the positive electrode mixture; it can range from 0.0005% to 7% by mass.

[0055] The positive electrode mixture may contain a solvent from the electrolyte. Examples of solvents include dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate.

[0056] [Recovery of the positive electrode mixture]

[0057] The positive electrode flux can be obtained by separating and recovering the positive electrode flux layer from a waste positive electrode that has a current collector and a positive electrode flux layer.

[0058] "Waste positive electrode" can be positive electrode recycled from discarded batteries, or waste generated during the manufacturing process of positive electrodes or batteries. Discarded batteries can be used batteries or unused but defective batteries. Waste positive electrode can be the end of a positive electrode generated during the battery manufacturing process or a defective positive electrode. As a positive electrode binder, waste of positive electrode binder not attached to the current collector (waste generated during the positive electrode binder manufacturing process) can also be used.

[0059] The waste positive electrode has a current collector made of metal foil such as aluminum foil or copper foil, and a positive electrode flux layer disposed on the current collector. The positive electrode flux layer can be disposed on one side of the current collector or on both sides.

[0060] Examples of methods for separating the positive electrode flux layer from a waste positive electrode having a current collector and a positive electrode flux layer include methods such as mechanically peeling the positive electrode flux layer from the current collector (e.g., scraping the positive electrode flux layer off the current collector), peeling the positive electrode flux layer from the current collector by allowing a solvent to penetrate to the interface between the current collector and the positive electrode flux layer, and separating the positive electrode flux layer by dissolving the current collector using an alkaline or acidic aqueous solution. The preferred method for separating the positive electrode flux layer from a waste positive electrode having a current collector and a positive electrode flux layer is the method of mechanically peeling the positive electrode flux layer from the current collector.

[0061] Previous process (B): Cleaning process of positive electrode mixture

[0062] Next, if the positive electrode mixture contains an electrolyte, it is preferable to contact the prepared positive electrode mixture with an electrolyte cleaning solvent to remove at least a portion of the electrolyte from the positive electrode mixture. Specifically, the positive electrode mixture containing the positive electrode active material and the electrolyte is contacted with an electrolyte cleaning solvent to obtain a slurry containing solid and liquid components, and then the slurry is separated into solid and liquid components.

[0063] Solid-liquid separation is the process of separating a slurry into solid and liquid components. Examples of solid-liquid separation methods include conventionally known methods such as filtration and centrifugation.

[0064] There are no particular restrictions on the solvents used for electrolyte cleaning. Examples of electrolyte cleaning solvents include carbonates such as ethylene carbonate, dimethyl carbonate, methyl ethyl carbonate, diethyl carbonate, and propylene carbonate; water; ketones such as acetone, methyl ethyl ketone, diethyl ketone, and methyl isobutyl ketone; and alcohols such as ethanol, methanol, propanol, and isopropanol.

[0065] Contacting the electrolyte cleaning solvent with the positive electrode agent can be carried out in a known contact device for powder and liquid (e.g., a stirred tank).

[0066] In the process of contacting the positive electrode mixture with the electrolyte cleaning solvent, it is preferable to stir the positive electrode mixture and the electrolyte cleaning solvent to obtain a slurry. The circumferential speed of the tip of the stirring blade can be 0.1~1.0 m / s.

[0067] In the cleaning process of the positive electrode mixture, the solid components can be rinsed after solid-liquid separation. Rinsing involves bringing the electrolyte cleaning solvent back into contact with the solid components to obtain a slurry, and then separating the slurry back into solid and liquid components. Multiple rinsings can be performed in the cleaning process of the positive electrode mixture. The slurry concentration during rinsing can be adjusted arbitrarily. The slurry can also be stirred during rinsing as described above.

[0068] The above cleaning process can effectively remove electrolyte from the positive electrode mixture. For example, when electrolyte remains, the following reaction occurs, sometimes changing the structure of the positive electrode active material from a layered rock salt structure to a spinel structure. However, by removing electrolyte from the positive electrode mixture, this reaction can be suppressed. LiPF6+16LiMO2+2O2→6LiF+Li3PO4+8LiM2O4

[0069] In addition, when the activator contains lithium carbonate, lithium consumption may sometimes occur due to the following reaction, but this reaction can be suppressed by removing the electrolyte from the positive electrode mixture. LiPF6+4Li2CO3→6LiF+Li3PO4+4CO2

[0070] The separated solid components can be dried using the electrolyte washing solvent by depressurization and / or heating, if necessary. The heating temperature can be 50~200℃.

[0071] Process (1): Mixing of activating agents

[0072] Next, the prepared positive electrode mixture is mixed with an activating agent containing one or more alkaline compounds to obtain a mixture.

[0073] The mixing method for the positive electrode agent and the activating agent can be either dry mixing or wet mixing, or a combination of their mixing methods. There are no particular restrictions on the mixing order of the positive electrode agent and the activating agent.

[0074] During mixing, it is preferable to use a mixing device equipped with a mixing medium such as balls for crushing and mixing, thereby improving mixing efficiency.

[0075] As a mixing method, dry mixing is preferred from the perspective of being easier to perform. In dry mixing, powder mixers equipped with V-type mixers, W-type mixers, ribbon mixers, drum mixers, stirring blades, ball mills, vibratory mills, or combinations of these devices can be used.

[0076] As a mixing device used in dry mixing, a powder mixer with internal stirring blades is preferred. Specifically, the Loedige mixer (manufactured by Matsubo Co., Ltd.) can be cited as an example.

[0077] The activation agent used in this process will be described in detail below.

[0078] <Activating agent>

[0079] The activating agent contains one or more alkali metal compounds. Preferably, the activating agent contains at least one compound selected from potassium and sodium compounds. Here, potassium and / or sodium are sometimes referred to as alkali metal element X. In addition to potassium and / or sodium compounds, the activating agent may also contain alkali metal compounds including other alkali metals such as Li.

[0080] When the activating agent comes into contact with the positive electrode active material, it can activate the positive electrode active material. In cases where the activating agent contains an alkali metal compound, particularly a molten portion, the activation of the positive electrode active material can be further promoted by increasing the contact between the molten portion and the positive electrode active material.

[0081] Furthermore, the positive electrode mixture sometimes contains fluorine-containing compounds from the binder and / or electrolyte. However, by contacting the fluorine-containing compounds with the activating agent, the fluorine component is stabilized as an alkali metal fluoride, thus suppressing the generation of corrosive gases such as hydrogen fluoride. It should be noted that hydrogen fluoride is also preferably prevented because it reduces the activity of the positive electrode active material.

[0082] The proportion of all alkali metal compounds in the activator can be appropriately set considering the type of alkali metal compound, the type of positive electrode active material to be targeted, etc., and can usually be 50% by mass or more, preferably 70% by mass or more, and can be 100% by mass (in the case that the activator is essentially composed of alkali metal compounds).

[0083] The concentration of at least one alkali metal selected from potassium and sodium in the alkali metal compound can be adjusted arbitrarily from 0 to 100 mol%, preferably 10 mol% or more, more preferably 20 mol% or more, more preferably 90 mol% or less, and more preferably 80 mol% or less.

[0084] Examples of alkali metal compounds that can serve as activating agents include alkali metal hydroxides, borates, carbonates, oxides, peroxides, superoxides, nitrates, phosphates, sulfates, chlorides, vanadates, hydrobromates, molybdates, and tungstates. These components can be used individually or in combination.

[0085] Specific examples of preferred alkali metal compounds include: Hydroxides such as LiOH, NaOH, KOH, RbOH, and CsOH; Borates such as LiBO2, NaBO2, KBO2, RbBO2, and CsBO2; Carbonates such as Li2CO3, Na2CO3, K2CO3, RbCO3, and CsCO3; Oxides such as Li₂O, Na₂O, K₂O, Rb₂O, and Cs₂O; Peroxides such as Li2O2, Na2O2, K2O2, Rb2O2, and Cs2O2; Superoxides such as LiO2, NaO2, KO2, RbO2, and CsO2; Nitrates such as LiNO3, NaNO3, KNO3, RbNO3, and CsNO3; Phosphates such as Li3PO4, Na3PO4, K3PO4, Rb3PO4, and Cs3PO4; Sulfates such as Li2SO4, Na2SO4, K2SO4, Rb2SO4, and Cs2SO4; Chlorides such as LiCl, NaCl, KCl, RbCl, and CsCl; Bromides such as LiBr, NaBr, KBr, RbBr, and CsBr; Vanadates such as LiVO3, NaVO3, KVO3, RbVO3, and CsVO3; Molybdates such as Li₂MoO₄, Na₂MoO₄, K₂MoO₄, Rb₂MoO₄, and CsMoO₄; and Tungstates such as Li2WO4, Na2WO4, K2WO4, Rb2WO4, and CsWO4.

[0086] In order to further improve the activation effect of the positive electrode active material, the activating agent may contain an alkali metal element that is the same as the alkali metal element contained in the positive electrode active material in the positive electrode mixture, in addition to at least one compound selected from potassium compounds and sodium compounds.

[0087] That is, when the positive electrode active material in the positive electrode mixture is a lithium composite oxide, the activating agent preferably includes a lithium compound in addition to at least one compound selected from potassium and sodium compounds. Examples of suitable lithium compounds include LiOH, LiBO2, Li2CO3, Li2O, Li2O2, LiO2, LiNO3, Li3PO4, Li2SO4, LiCl, LiVO3, LiBr, Li2MoO4, and Li2WO4.

[0088] The activating agent may contain compounds other than alkali metal compounds as needed. Examples of compounds other than alkali metal compounds include alkaline earth metal compounds containing alkaline earth metal elements such as magnesium, calcium, and barium. The alkaline earth metal compounds are included in the activating agent along with the alkali metal compounds to control the melting start temperature of the activating agent.

[0089] In addition, the content of compounds other than alkali metal compounds in the activating agent is selected within a range that does not significantly inhibit the effect of the molten alkali metal compounds mentioned above, and may be less than 50% by mass relative to the total mass of the activating agent.

[0090] The amount of activating agent added to the mixture of positive electrode agent and activating agent is preferably 0.001 to 100 times, more preferably 0.05 to 1 times, relative to the mass of the positive electrode active material contained in the positive electrode mixture.

[0091] When the activating agent contains potassium and lithium compounds, the ratio of lithium content (mol basis) to potassium content (mol basis) (lithium content / potassium content) can be 0.01~100, 0.1~10, or 0.2~4, from the viewpoint that it is easy to make the charge-discharge characteristics of batteries made using recycled positive electrode active materials more similar to those of batteries made using unused positive electrode active materials.

[0092] When the activating agent contains sodium and lithium compounds, the ratio of lithium content (mol basis) to sodium content (mol basis) (lithium content / sodium content) can be 0.01~100, 0.1~10, or 0.2~4, from the viewpoint that it is easy to make the charge-discharge characteristics of batteries made using recycled positive electrode active materials more similar to those of batteries made using unused positive electrode active materials.

[0093] When the activator contains a potassium compound, from the viewpoint that it is easy to make the charge-discharge characteristics of a battery made using recycled positive electrode active material more similar to those of a battery made using unused positive electrode active material, the potassium content (mol basis) in the activator relative to the fluorine content (mol basis) in the positive electrode compound can be 1% or more and less than 500%, 10% or more and less than 400%, 50% or more and less than 300%, 100% or more and less than 250%, or 150% or more and less than 250%.

[0094] When the activator contains a sodium compound, from the viewpoint that it is easy to make the charge-discharge characteristics of a battery made using recycled positive electrode active material more similar to those of a battery made using unused positive electrode active material, the sodium content (mol basis) in the activator relative to the fluorine content (mol basis) in the positive electrode compound can be 1~200%, 10~200%, 50~200%, or 100~200%, 1% or more but less than 150%, 10% or more but less than 150%, 50% or more but less than 150%, or 100% or more but less than 150%.

[0095] The molar number of alkali metal compounds in the activator of the mixture of positive electrode agent and activator can be added in such a way that the molar number of alkali metal elements is 0.001 to 200 times when the molar number of positive electrode active material (e.g., Formula A) contained in the positive electrode agent is set to 1.

[0096] By appropriately controlling the proportion of activating agents in the mixture, the cost of recovering positive electrode active materials from the positive electrode mixture can be reduced, and the oxidation and decomposition rate of carbon-based conductive materials and binders can be increased. Furthermore, the effect of preventing the generation of corrosive gases during the heating process can be improved, thereby further increasing the discharge capacity of batteries manufactured using the obtained positive electrode active materials.

[0097] Furthermore, at least one of the alkali metal compounds contained in the activating agent is preferably an alkali metal compound that exhibits alkalinity when dissolved in water. An activating agent containing such an alkali metal compound produces a solution with a pH greater than 7 when dissolved in pure water. Hereinafter, such an activating agent will sometimes be referred to as an "alkaline activating agent."

[0098] By using an alkaline activating agent, the generation of corrosive gases during the heating process can be further suppressed, thus further improving the discharge capacity of batteries manufactured using recycled positive electrode active materials. Furthermore, using an alkaline activating agent can also increase the processing speed of carbon-based conductive materials and binders.

[0099] Examples of alkali metal compounds that exhibit alkalinity when dissolved in water containing an alkaline activating agent include alkali metal hydroxides, carbonates, bicarbonates, oxides, peroxides, and superoxides. Specifically, examples of alkali metal compounds exhibiting alkalinity include hydroxides such as LiOH, NaOH, KOH, RbOH, and CsOH; carbonates such as Li₂CO₃, Na₂CO₃, K₂CO₃, RbCO₃, and CsCO₃; bicarbonates such as LiHCO₃, NaHCO₃, KHCO₃, RbHCO₃, and CsHCO₃; oxides such as Li₂O, Na₂O, K₂O, Rb₂O, and Cs₂O; peroxides such as Li₂O₂, Na₂O₂, K₂O₂, Rb₂O₂, and Cs₂O₂; and superoxides such as LiO₂, NaO₂, KO₂, RbO₂, and CsO₂. One or more of these compounds may be included in the activating agent.

[0100] Furthermore, when the conductive material contained in the positive electrode mixture is a carbon-based conductive material, at least one of the alkali metal compounds contained in the activating agent may be an alkali metal compound that has oxidizing power to decompose the carbon-based conductive material at the temperature of the heating process. Hereinafter, the activating agent containing such an alkali metal compound is sometimes referred to as an "activating agent with oxidizing power".

[0101] When such an activating agent with oxidizing power is used, it is particularly effective in promoting the oxidation of carbon materials, i.e. conductive materials, into carbon dioxide, and in promoting the oxidation of binders, which are hydrocarbon materials, into carbon dioxide and water vapor. This can further improve the discharge capacity of batteries manufactured using the obtained positive electrode active material, and in some cases, can improve the effect of preventing the generation of corrosive gases during the heating process.

[0102] Alkali metal compounds that possess the oxidizing power required to oxidize carbon-based conductive materials and hydrocarbons into carbon dioxide and water vapor include alkali metal peroxides, superoxides, nitrates, sulfates, vanadates, and molybdates. One or more of these compounds may be used.

[0103] As alkali metal compounds with oxidizing power, examples include superoxides such as Li₂O₂, Na₂O₂, K₂O₂, Rb₂O₂, and Cs₂O₂; nitrates such as LiO₂, NaO₂, KO₂, RbO₂, and CsO₂; sulfates such as Li₂SO₄, Na₂SO₄, K₂SO₄, Rb₂SO₄, and Cs₂SO₄; vanadates such as LiVO₃, NaVO₃, KVO₃, RbVO₃, and CsVO₃; and molybdates such as Li₂MoO₄, Na₂MoO₄, K₂MoO₄, Rb₂MoO₄, and CsMoO₄.

[0104] Details of the oxidizing power of these alkali metal compounds are described in Japanese Patent Application Publication No. 2012-186150.

[0105] From the viewpoint that it is easy to make the rate characteristics of batteries made using recycled positive electrode active materials more similar to those of batteries made using unused positive electrode active materials, the alkali metal compound can be a carbonate or a sulfate, or at least one selected from Li2CO3, Na2SO4, Na2CO3 and K2CO3.

[0106] Process (2): Heating process

[0107] The heating process is a process of heating the mixture obtained in process (1) (hereinafter sometimes referred to as "the mixture before heating") at a temperature T℃. Sometimes the mixture obtained in this heating process is referred to as "the mixture after heating".

[0108] The temperature T can be lower than or higher than the melting start temperature (Tmp) of the activating agent. In this specification, "temperature T lower than the melting start temperature (Tmp) of the activating agent" means heating the mixture before heating to a temperature lower than the melting start temperature of the activating agent while maintaining the temperature at a temperature lower than the melting start temperature of the activating agent (heating at a holding temperature lower than the melting start temperature of the activating agent). Heating to a temperature lower than the melting start temperature of the activating agent means heating the mixture before heating at a temperature not higher than the melting start temperature of the activating agent. Furthermore, heating the mixture before heating to a temperature higher than the melting start temperature of the activating agent means heating while maintaining the temperature at a temperature higher than the melting start temperature of the activating agent (heating at a holding temperature higher than the melting start temperature of the activating agent).

[0109] It should be noted that the "melting start temperature (Tmp) of the activating agent" refers to the lowest temperature at which a portion of the activating agent is in the liquid phase.

[0110] The melting start temperature (Tmp) of the activating agent was determined by differential calorimetry (DTA). Specifically, 5 mg of the mixture before heating was subjected to differential calorimetry (DTA, measurement conditions: heating rate: 10℃ / min), and the temperature at which the DTA signal showed an endothermic peak was taken as the melting start temperature (Tmp).

[0111] In step (2), by heating the mixture before heating to a temperature lower than the melting start temperature (Tmp) of the activator, the following effect occurs. Therefore, from the viewpoint that by suppressing the dissolution of metals in the positive electrode active material into the molten salt reaction field of the activator, it is easier to achieve the same rate characteristics as batteries manufactured using unused positive electrode active materials, the temperature T is preferably lower than the melting start temperature (Tmp) of the activator.

[0112] By heating the mixture before heating to a temperature below the melting start temperature (Tmp) of the activator, hydrogen fluoride and carbon dioxide generated during the decomposition of binder materials, conductive materials, etc., contained in the positive electrode mixture are rapidly produced. These substances come into contact with the positive electrode active material, thereby inhibiting the degradation of the crystal structure of the positive electrode active material and making it easier to achieve charge-discharge characteristics similar to those of batteries made using unused positive electrode active materials. Furthermore, by heating the mixture before heating together with the activator, a crystal structure repair effect can also be achieved.

[0113] By heating the mixture before heating to a temperature above the melting start temperature (Tmp) of the activating agent, at least a portion of the activating agent melts. By bringing the molten activating agent into contact with the positive electrode active material, the crystal structure of the positive electrode active material can also be repaired.

[0114] By contacting the molten activator with carbon-based conductive materials and binders, the rate of oxidative decomposition of the conductive and binder materials is increased. Furthermore, the molten activator comes into contact with fluorine compounds from the binder and electrolyte, thereby stabilizing the fluorine component as an alkali metal fluoride, preventing the generation of hydrogen fluoride, a corrosive gas, and further suppressing the deterioration of the crystal structure of the positive electrode active material.

[0115] Furthermore, even when the activating agent contains the same alkali metal as the positive electrode active material, it can also supply the insufficient alkali metal to the positive electrode active material.

[0116] Based on the view that hydrogen fluoride and carbon dioxide generated from the decomposition of binder materials, conductive materials, etc. contained in the positive electrode compound are rapidly produced, and that these react with the positive electrode active material to inhibit the degradation of the crystal structure of the positive electrode active material, and to more easily achieve the same rate characteristics as batteries made using unused positive electrode active materials, the temperature T can be below 700°C, below 650°C, below 600°C, or below 550°C.

[0117] From the perspective of promoting the decomposition of binders, conductive materials, etc., and making it easier to achieve the same rate characteristics as batteries made using unused positive electrode active materials, the temperature T can be above 150°C, above 200°C, above 250°C, above 300°C, above 350°C, above 400°C, or above 450°C.

[0118] The melting start temperature (Tmp) of the activating agent is preferably below 900°C, more preferably below 800°C, further preferably below 700°C, and particularly preferably below 600°C. The melting start temperature (Tmp) of the activating agent has no lower limit, and can be, for example, above 150°C, above 250°C, above 350°C, above 450°C, or above 500°C.

[0119] The melting point of an activator refers to the lowest temperature at which a portion of the activator becomes liquid when heated alone. By mixing the positive electrode agent with the activator, the melting onset temperature (Tmp) of the activator becomes lower than its melting point.

[0120] The melting point of the activator was determined by differential calorimetry (DTA). Specifically, 5 mg of the activator was subjected to differential calorimetry (DTA, measurement conditions: heating rate: 10 °C / min), and the temperature at which the DTA signal showed an endothermic peak was taken as the melting point of the activator.

[0121] The atmosphere used for heating is not particularly limited and can be oxygen-containing gases such as air, nitrogen, argon, or carbon dioxide. The pressure of the atmosphere is not particularly limited and can be atmospheric pressure, a depressurized atmosphere, or a pressurized atmosphere.

[0122] The temperature T and the holding time at temperature T can be appropriately adjusted by the types and combinations of alkali metal compounds and other compounds contained in the positive electrode active material, binder, conductive material, and activating agent constituting the positive electrode mixture. Typically, the temperature T is in the range of 100~1000℃, and the holding time is about 10 minutes to 24 hours.

[0123] The preferred temperature T is lower than the melting point of the alkali metal compound contained in the activating agent. It should be noted that the melting point of the alkali metal compound may sometimes be lower than the melting point of the individual compounds when multiple compounds are mixed. When the activating agent contains two or more alkali metal compounds, the eutectic point is used as the melting point of the alkali metal compound.

[0124] After the heating process, the mixture can be cooled to any temperature (e.g., room temperature (20°C)) as needed. This yields a heated mixture containing the heated positive electrode active material.

[0125] Process (3): Positive electrode active material recovery process The positive electrode active material recovery process is a process that, after the heating process in process (2), heats the heated mixture (or the solid components obtained in process (3a) or process (3b) at a higher temperature than that in process (2) to recover the heated positive electrode active material.

[0126] The heated mixture contains, in addition to the heated positive electrode active material, components from the activating agent (alkali metal compounds, etc.), unreacted activating agent, undecomposed conductive material, binder, and undecomposed products of other positive electrode agents. Furthermore, in cases where the positive electrode agent contains an electrolyte containing fluorine, it may also contain fluorine components from the electrolyte. In step (3), from the viewpoint that it is easier to achieve rate characteristics similar to those of a battery manufactured using unused positive electrode active material by increasing the purity of the positive electrode active material, it is preferable to remove components from the activating agent (alkali metal compounds, etc.), unreacted activating agent, undecomposed conductive material, binder, and undecomposed products of other positive electrode agents.

[0127] Methods for separating and recovering heated positive electrode active material from heated mixtures include solid-liquid separation, which involves adding a solvent such as water to the mixture to make it into a slurry and then separating the solid and liquid components, and gasification separation, which involves heating the mixture to vaporize components other than the heated positive electrode active material and then separating them.

[0128] The solid-liquid separation method will be explained below.

[0129] Process (3a): Solid-liquid separation process

[0130] Step (3a) involves contacting the heated mixture with a water-containing liquid to obtain a slurry containing solid components (the heated mixture or the solid components of the heated positive electrode active material) and liquid components, and then separating the slurry into solid and liquid components.

[0131] The heated mixture contains, in addition to the heated positive electrode active material, components from the activating agent (alkali metal compounds, etc.), undecomposed conductive materials, and undecomposed products of the positive electrode binder, etc. Furthermore, in cases where the positive electrode binder contains an electrolyte containing fluorine, it may also contain fluorine components from the electrolyte.

[0132] In order to separate and recover the heated positive electrode active material from the heated mixture, an aqueous liquid is added to the mixture and slurryed before solid-liquid separation is performed to separate the solid and liquid components.

[0133] In the slurry preparation process (the process of contacting a heated mixture with an aqueous liquid to obtain a slurry containing both solid and liquid components), there are no particular restrictions on the liquid used, as long as it contains water. The amount of water in the liquid can be 50% by mass or more. To improve the solubility of water-soluble components or to increase the processing speed, components other than water can be added to the liquid to adjust the pH.

[0134] Preferred examples of liquids containing water include pure water and alkaline cleaning solutions. Examples of alkaline cleaning solutions include aqueous solutions of one or more acid anhydrides and their hydrates selected from lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, and ammonium carbonate. Ammonia can also be used as a base.

[0135] The resulting slurry comprises a solid component mainly consisting of the heated positive electrode active material and a liquid component consisting of water-soluble components other than the positive electrode active material. It should be noted that the liquid component contains alkali metal components derived from the activating agent and / or fluorine components derived from the binder and electrolyte.

[0136] The amount of liquid in contact with the mixture is appropriately determined by taking into account the amounts of the heated positive electrode active material and the water-soluble components other than the positive electrode active material contained in the mixture.

[0137] In step (3a), it is preferable to stir the heated mixture and the water-containing liquid to obtain a slurry. This promotes the dissolution of water-soluble components. The circumferential speed of the tip of the stirring blade is preferably set to 0.1~0.9 m / s.

[0138] The slurry obtained in the pulping process is then subjected to solid-liquid separation. Solid-liquid separation refers to the operation of separating the slurry into liquid and solid components. Methods for solid-liquid separation can be conventionally known methods, such as filtration and centrifugation.

[0139] In step (3a), the obtained solid components can be rinsed after solid-liquid separation. Rinsing refers to the operation of bringing the liquid containing water into contact with the obtained solid components again to obtain a slurry, and then separating the slurry into solid and liquid components again. Multiple rinsings can be performed in step (3a). The slurry concentration in rinsing can also be the same as the slurry concentration in the solid-liquid separation step described above.

[0140] Process (3b): Drying process

[0141] Process (3b) is, for example, a process of removing water from solid components by exposing them to a heated and / or depressurized environment.

[0142] In the drying process, the heating temperature is preferably 100°C or higher to remove water. For further thorough water removal, it is preferably set to 150°C or higher. Particularly, temperatures above 250°C result in a further increase in the discharge capacity of the battery manufactured using the obtained positive electrode active material, and are therefore preferred. The temperature in the drying process can be constant, or it can be varied in stages or continuously. The heating temperature range can, for example, be 10°C or higher and below 900°C.

[0143] The pressure range for pressure reduction can be, for example, 1.0 × 10⁻⁶. -10 ~1.0×10 3 Pa.

[0144] Process (3c): Annealing process

[0145] Step (3c) is a step of heating the heated mixture (or the solid components obtained in step (3a) or step (3b) at a temperature higher than that of step (2).

[0146] In one embodiment, when the temperature in step (2) is T℃, the temperature at which the heated mixture is heated is (1.6×T)℃ or higher. By heating the heated mixture to a temperature of (1.6×T)℃ or higher, the rate characteristics of a battery manufactured using recycled positive electrode active material can be made to be the same as those of a battery manufactured using unused positive electrode active material.

[0147] In other embodiments, when the temperature in step (2) is T℃, the temperature at which the heated mixture is heated is (T+300)℃ or higher. By heating the heated mixture to a temperature of (T+300)℃ or higher, it is possible to make the rate characteristics of a battery manufactured using recycled positive electrode active material the same as those of a battery manufactured using unused positive electrode active material. That is, another embodiment of the method for manufacturing recycled positive electrode active material of this disclosure includes the following steps. Step (1): A process of mixing a positive electrode mixture containing a positive electrode active material and a binder with an activating agent containing one or more alkali metal compounds to obtain a mixture. Step (2): Heating the mixture at temperature T℃ to obtain the heated mixture. Step (3): Heating the heated mixture at a temperature above (T+300)℃ to recover the heated positive electrode active material.

[0148] Regarding the temperature of the heated mixture in the annealing process (e.g., (1.6×T) or (T+300)), from the viewpoint of removing impurities by vaporizing components other than the positive electrode active material, and from the viewpoint of making it easier to achieve rate characteristics similar to those of batteries manufactured using unused positive electrode active materials by sufficiently increasing the microcrystal size of the positive electrode active material, it can exceed 700°C, 750°C or more, 800°C or more, 850°C or more, or 900°C or more.

[0149] From the viewpoint that it is easier to achieve charge-discharge characteristics similar to those of batteries manufactured using unused positive electrode active materials by sufficiently increasing the crystallite size of the positive electrode active material, the temperature at which the heated mixture is heated in the annealing process can be above the melting start temperature of the activating agent. In the annealing process, the heated mixture can be heated at a temperature 20°C, 30°C, 40°C, 50°C, 100°C, 150°C, or 200°C higher than the melting start temperature of the activating agent.

[0150] In the annealing process, from the viewpoint of suppressing the heat-induced degradation of the positive electrode active material and thus more easily achieving the same rate characteristics as batteries manufactured using unused positive electrode active materials, the temperature at which the heated mixture is heated (e.g., (1.6×T) or (T+300)) can be below 1500°C, below 1400°C, below 1300°C, below 1200°C, below 1000°C, or below 950°C.

[0151] When the heating temperature of step (2) is set to T1 and the heating temperature of step (3) is set to T2, from the viewpoint that it is easier to achieve the same rate characteristics as batteries manufactured using unused positive electrode active materials, T2 / T1 can be 1.7 or more, 1.8 or more, 1.9 or more, or 2 or more. From the same viewpoint, it can be 2.5 or less, 2.4 or less, 2.3 or less, or 2.2 or less. That is, when the heating temperature of step (2) is T℃, the heating temperature of step (3) can be (1.7×T)℃ or more, (1.8×T)℃ or more, (1.9×T)℃ or more, or (2×T)℃ or more, or (2.5×T)℃ or less, (2.4×T)℃ or less, (2.3×T)℃ or less, or (2.2×T)℃ or less.

[0152] When the heating temperature of step (2) is set to T1 and the heating temperature of step (3) is set to T2, from the viewpoint that it is easier to achieve the same level of charge and discharge characteristics as batteries manufactured using unused positive electrode active materials, T2-T1 can be above 350°C, above 400°C, above 450°C, or above 500°C. From the same viewpoint, it can be below 1000°C, below 800°C, below 700°C, below 600°C, or below 500°C. That is, when the heating temperature of step (2) is T°C, the heating temperature of step (3) can be above (T+350)°C, above (T+400)°C, above (T+450)°C, or above (T+500)°C, or below (T+1000)°C, below (T+800)°C, below (T+700)°C, below (T+600)°C, or below (T+500)°C.

[0153] In the annealing process, the heat treatment atmosphere is not particularly limited, but it is preferably an oxygen-containing atmosphere such as air. The holding time of the heat treatment can be set from 1 minute to 24 hours. It is particularly preferred to heat at a temperature higher than that of process (2) for 0.1 hours or more and 5 hours or less.

[0154] The recycled positive electrode active material obtained from the battery compound using the method for manufacturing recycled positive electrode active material disclosed herein can be utilized in the same way as unused positive electrode active material. The method for manufacturing a positive electrode and battery using recycled positive electrode active material is the same as the method for manufacturing a positive electrode and battery using unused positive electrode active material, and is well known.

[0155] The rate capability of a battery manufactured using the positive electrode active material obtained by the method for manufacturing recycled positive electrode active material according to one embodiment of this disclosure is to the same extent as that of a battery manufactured using unused positive electrode active material. Specifically, for example, when a battery manufactured using the positive electrode active material obtained by the method for manufacturing recycled positive electrode active material according to one embodiment is charged at a constant current of 0.2C to a maximum charging voltage of 4.3V at 25°C, and then discharged at a constant current of 0.5C, 1C, 2C, 3C, or 5C to a minimum discharge voltage of 2.5V, the recycling rate of the discharge capacity (discharge capacity of a battery manufactured using recycled positive electrode active material / discharge capacity of a battery manufactured using unused positive electrode active material) is 0.9 to 1.1, which is equivalent to the charging capacity of a battery manufactured using unused positive electrode active material.

[0156] In this specification, the positive electrode active material that has undergone steps (1) to (3) is referred to as a recycled positive electrode active material. The recycled positive electrode active material that has undergone steps (1) to (3) is suitable for use in the manufacture of positive electrodes, etc. The manufacturing method of the recycled positive electrode active material may include additional steps before or after steps (1) to (3). In this specification, the positive electrode active material that has undergone additional steps other than steps (1) to (3) is also referred to as a recycled positive electrode active material. Examples of additional steps other than steps (1) to (3) are the preceding steps (A) and (B) performed before step (1).

[0157] [Example]

[0158] The present disclosure will now be described in more detail through examples, but the present disclosure is not limited to the following examples as long as its spirit remains unchanged.

[0159] <The Manufacturing of the Positive Electrode>

[0160] The positive electrode described below is prepared according to the following steps. A mixture is obtained by mixing 90 parts by weight of positive electrode active material (unused positive electrode active material or recycled positive electrode active material), 3 parts by weight of binder (manufactured by KUREHA Co., Ltd., product number: PVdF#1100), and 7 parts by weight of carbon black (conductive material, manufactured by Denka Co., Ltd., product number: HS100). As the binder PVdF, a binder solution prepared by dissolving PVdF in NMP (N-methyl-2-pyrrolidone) is used. The mixture is kneaded in an agate mortar to prepare a positive electrode slurry. NMP is added to adjust the positive electrode slurry to a total mass of 52% by weight of the positive electrode active material, binder, and conductive material.

[0161] On one side of a 20μm thick aluminum foil 1085 (manufactured by Nippon Foil Co., Ltd.) used as the positive electrode current collector in a lithium-ion secondary battery, the concentration of the positive electrode active material was 10.0±0.2 mg / cm³. 2 After coating the positive electrode slurry using a specific method, it was vacuum dried at 150°C for 8 hours to obtain the positive electrode. The electrode area of ​​this positive electrode is 1.65 cm². 2 .

[0162] <Battery Manufacturing>

[0163] The coin-shaped battery described below is manufactured according to the following steps. The above-described positive electrode, electrolyte, separator, and negative electrode are combined to manufacture a coin-shaped battery (non-aqueous electrolyte secondary battery). Battery assembly is performed in a glove box under an argon atmosphere. As the electrolyte, a solution of LiPF6 dissolved in a 30:35:35 (volume ratio) mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate at a ratio of 1.0 mol / L is used. As the separator, a laminated thin-film separator formed by stacking heat-resistant porous layers on a porous thin film (made of polyethylene) is used. As the negative electrode, metallic lithium is used.

[0164] Manufacturing the positive electrode before recycling

[0165] As the positive electrode active material, it is prepared to have a composition of Li 1.05 Ni 0.34 Co 0.33 Mn 0.33 O2 and NCM111, a positive electrode active material with an R-3m crystal structure, were used. This positive electrode active material has a rated capacity of 160 mAh / g and a 1C current of 160 mA / g. A coin-shaped battery was fabricated using this unused positive electrode active material. The battery was charged at a constant current of 0.2C to the maximum charging voltage of 4.3V at 25°C, and then discharged at constant currents of 0.5C, 1C, 2C, 3C, and 5C to the minimum discharge voltage of 2.5V. The discharge capacity during rate testing was measured. The results are shown in Table 1.

[0166] (Example 1)

[0167] From the positive electrode produced during the manufacturing of the aforementioned positive electrode, the electrode compound is mechanically shaved off, stripping it from the current collector. 30g of the electrode compound removed from the positive electrode is mixed with 10 mol of Li₂CO₃ (relative to 100 mol of the positive electrode active material) and 10 mol of Na₂SO₄ (relative to 100 mol of the positive electrode active material) as an activating agent to obtain a mixture (mixture before heating). The melting start temperature of the activating agent is 510°C.

[0168] Place 30g of the mixture before heating into an electric furnace and heat it in air at a heating rate of 300℃ / h, a heating temperature of 450℃ (lower than the melting start temperature of the activator), and a heating time of 360 minutes.

[0169] The heated mixture was pulverized, distilled water was added, and the mixture was stirred to obtain a slurry. The slurry was then filtered to separate the solid and liquid components. The solid component was then recovered and dried under reduced pressure at 100°C for 1 hour.

[0170] The dried solid component was placed in an electric furnace and heated in air at a temperature of 900°C for 60 minutes to obtain the heated recycleable positive electrode active material. The heated recycleable positive electrode active material was then allowed to cool naturally to room temperature (20°C), and it was confirmed that the composition, crystal structure, average particle size, and specific surface area of ​​the obtained recycleable positive electrode active material were identical to those of the unused positive electrode active material. The above-mentioned coin-shaped battery was fabricated using the recycleable positive electrode active material, and rate tests were conducted at 0.5C, 1C, 2C, 3C, and 5C current values ​​while maintaining a temperature of 25°C. The test results are shown in Table 1.

[0171] (Example 2)

[0172] The temperature of the dried heated solid component was changed to 950°C, and otherwise, the recycled positive electrode active material was obtained in the same manner as in Example 1. The composition, crystal structure, average particle size, and specific surface area of ​​the obtained recycled positive electrode active material were identical to those of the unused positive electrode active material. The above-mentioned coin-shaped battery was fabricated using the recycled positive electrode active material, and rate tests were conducted at current values ​​of 0.5C, 1C, 2C, 3C, and 5C while maintaining a temperature of 25°C. The test results are shown in Table 1.

[0173] (Example 3)

[0174] As an activating agent, 10 mol of Na₂CO₃ (melting start temperature: 851°C) relative to 100 mol of the positive electrode active material was used. 5 g of the electrode mixture taken from the positive electrode was mixed with the activating agent to obtain a mixture before heating. Otherwise, the recycled positive electrode active material was obtained in the same manner as in Example 1. The composition, crystal structure, average particle size, and specific surface area of ​​the obtained recycled positive electrode active material were similar to those of the unused positive electrode active material. The above-mentioned coin-shaped battery was fabricated using the recycled positive electrode active material, and rate tests were conducted at current values ​​of 0.5C, 1C, 2C, 3C, and 5C while maintaining 25°C. The test results are shown in Table 1.

[0175] (Example 4)

[0176] The temperature of the dried heated solid component was changed to 950°C, and otherwise, the recycled positive electrode active material was obtained in the same manner as in Example 3. The composition, crystal structure, average particle size, and specific surface area of ​​the obtained recycled positive electrode active material were identical to those of the unused positive electrode active material. The above-mentioned coin-shaped battery was fabricated using the recycled positive electrode active material, and rate tests were conducted at current values ​​of 0.5C, 1C, 2C, 3C, and 5C while maintaining a temperature of 25°C. The test results are shown in Table 1.

[0177] (Comparative Example 1)

[0178] The temperature at which the mixture was heated before heating was changed to 700°C (above the melting point), and the temperature at which the solid components were dried after heating was also changed to 700°C. Otherwise, the recycled positive electrode active material was obtained in the same manner as in Example 1. The composition, crystal structure, average particle size, and specific surface area of ​​the obtained recycled positive electrode active material were identical to those of the unused positive electrode active material. The above-described coin-shaped battery was fabricated using the recycled positive electrode active material, and rate tests were conducted at current values ​​of 0.5C, 1C, 2C, 3C, and 5C while maintaining a temperature of 25°C. The test results are shown in Table 1.

[0179] (Comparative Example 2)

[0180] The heating temperature of the mixture before heating was changed to 700°C (above the melting point), and otherwise, the recycled positive electrode active material was obtained in the same manner as in Example 1. The composition, crystal structure, average particle size, and specific surface area of ​​the obtained recycled positive electrode active material were identical to those of the unused positive electrode active material. The above-mentioned coin-shaped battery was fabricated using the recycled positive electrode active material, and rate tests were conducted at current values ​​of 0.5C, 1C, 2C, 3C, and 5C while maintaining a temperature of 25°C. The test results are shown in Table 1.

[0181] (Comparative Example 3)

[0182] The heating temperature of the mixture before heating was changed to 450°C (below the melting start temperature), and the temperature of the solid component after heating and drying was changed to 700°C. Otherwise, the recycled positive electrode active material was obtained in the same manner as in Example 1. The composition, crystal structure, average particle size, and specific surface area of ​​the obtained recycled positive electrode active material were identical to those of the unused positive electrode active material. The above-mentioned coin-shaped battery was fabricated using the recycled positive electrode active material, and rate tests were conducted at current values ​​of 0.5C, 1C, 2C, 3C, and 5C while maintaining a temperature of 25°C. The measurement results are shown in Table 1.

[0183] Manufacturing the positive electrode before recycling

[0184] As the positive electrode active material, it is prepared to have a composition of Li 1.18 Ni 0.34 Co 0.33 Mn 0.33O2 and NCM111, a positive electrode active material with an R-3m crystal structure, were used. This positive electrode active material has a rated capacity of 160 mAh / g and a 1C current of 160 mA / g. A coin-shaped battery was fabricated using this unused positive electrode active material. It was then charged at a constant current of 0.2C to the maximum charging voltage of 4.3V at 25°C, followed by constant current discharge at 0.5C, 1C, 2C, 3C, and 5C to the minimum discharge voltage of 2.5V. The discharge capacity during rate testing was measured. The results are shown in Table 2.

[0185] (Example 5)

[0186] From the positive electrode material produced during the manufacturing of the aforementioned positive electrode, the electrode mixture is mechanically shaved off to detach it from the current collector. 5g of the electrode mixture removed from the positive electrode is mixed with 10 mol of Li₂CO₃ (relative to 100 mol of the positive electrode active material) and 10 mol of Na₂SO₄ (relative to 100 mol of the positive electrode active material) as an activating agent to obtain a mixture (mixture before heating). The melting start temperature of the activating agent is 510°C.

[0187] 40g of the mixture before heating was placed in an electric furnace and heated in air at a heating rate of 300℃ / h, a heating temperature of 500℃ (lower than the melting point of the activator), and a heating time of 60 minutes. The air flow rate was set to 0.5L / min, and the gas-to-powder ratio was 5.8m. 3 / kg.

[0188] The heated mixture was pulverized, distilled water was added, and the mixture was stirred to obtain a slurry. The slurry was then filtered to separate the solid and liquid components. The solid component was then recovered and dried under reduced pressure at 100°C for 1 hour.

[0189] The dried solid component was placed in an electric furnace and heated in air at a temperature of 900°C for 360 minutes to obtain the heated recycleable positive electrode active material. The heated recycleable positive electrode active material was then allowed to cool naturally to room temperature (20°C), and it was confirmed that the composition, crystal structure, average particle size, and specific surface area of ​​the obtained recycleable positive electrode active material were identical to those of the unused positive electrode active material. The above-mentioned coin-shaped battery was fabricated using the recycleable positive electrode active material, and rate tests were conducted at 0.5C, 1C, 2C, 3C, and 5C current values ​​while maintaining a temperature of 25°C. The test results are shown in Table 2.

[0190] (Example 6)

[0191] The air flow rate for heating the mixture before heating was changed to 1 L / min, and the gas-to-powder ratio was changed to 11.5 m³ / min.3 / kg, except that, the recycled positive electrode active material was obtained in the same manner as in Example 5. The composition, crystal structure, average particle size, and specific surface area of ​​the obtained recycled positive electrode active material were similar to those of the unused positive electrode active material. The above-mentioned coin-shaped battery was made using the recycled positive electrode active material, and rate tests were conducted at current values ​​of 0.5C, 1C, 2C, 3C, and 5C while maintaining 25°C. The test results are shown in Table 2.

[0192] (Example 7)

[0193] The heating temperature of the mixture before heating was changed to 525°C, and otherwise, the recycled positive electrode active material was obtained in the same manner as in Example 6. The composition, crystal structure, average particle size, and specific surface area of ​​the obtained recycled positive electrode active material were similar to those of the unused positive electrode active material. The above-mentioned coin-shaped battery was fabricated using the recycled positive electrode active material, and rate tests were conducted at current values ​​of 0.5C, 1C, 2C, 3C, and 5C while maintaining 25°C. The test results are shown in Table 2.

[0194] (Example 8)

[0195] The heating temperature of the mixture before heating was changed to 550℃, the air flow rate was changed to 0.2L / min, and the gas-to-powder ratio was changed to 2.4m. 3 / kg, except that, the recycled positive electrode active material was obtained in the same manner as in Example 5. The composition, crystal structure, average particle size, and specific surface area of ​​the obtained recycled positive electrode active material were similar to those of the unused positive electrode active material. The above-mentioned coin-shaped battery was made using the recycled positive electrode active material, and rate tests were conducted at current values ​​of 0.5C, 1C, 2C, 3C, and 5C while maintaining 25°C. The test results are shown in Table 2.

[0196] (Comparative Example 4)

[0197] The amount of the mixture before heating was changed to 20g, the heating temperature of the mixture before heating was changed to 700℃, the heating time was changed to 360 minutes, the air flow rate was changed to 0.85L / min, and the gas-to-powder ratio was changed to 28.7m. 3 / kg, except that, the recycled positive electrode active material was obtained in the same manner as in Example 5. The composition, crystal structure, average particle size, and specific surface area of ​​the obtained recycled positive electrode active material were similar to those of the unused positive electrode active material. The above-mentioned coin-shaped battery was made using the recycled positive electrode active material, and rate tests were conducted at current values ​​of 0.5C, 1C, 2C, 3C, and 5C while maintaining 25°C. The test results are shown in Table 2.

[0198] (Comparative Example 5)

[0199] The temperature of the dried, heated solid component was changed to 950°C, and otherwise, a recycleable positive electrode active material was obtained in the same manner as in Comparative Example 4. The composition, crystal structure, average particle size, and specific surface area of ​​the obtained recycleable positive electrode active material were identical to those of the unused positive electrode active material. The above-mentioned coin-shaped battery was fabricated using the recycleable positive electrode active material, and rate tests were conducted at current values ​​of 0.5C, 1C, 2C, 3C, and 5C while maintaining a temperature of 25°C. The test results are shown in Table 2.

[0200] The heating temperature (T1) of the mixture before heating, the heating temperature (T2) of the dried solid component, the ratio of the heating temperature of the dried solid component to the heating temperature of the mixture before heating (T2 / T1), the difference between the heating temperature of the mixture before heating and the heating temperature of the dried solid component (T2-T1), and the results of the rate test (measured values ​​and recycling rate) for each embodiment and comparative example are shown in Table 1 and Table 2, respectively.

[0201]

[0202]

Claims

1. A method for manufacturing a recyclable positive electrode active material, comprising the following steps: (1) A process of mixing a positive electrode agent containing a positive electrode active material with an activating agent containing one or more alkali metal compounds to obtain a mixture; (2) The process of heating the mixture at a temperature T℃ to obtain the heated mixture; (3) The process of heating the heated mixture at a temperature above (1.6×T)℃ and recovering the heated positive electrode active material.

2. A method for manufacturing a recyclable positive electrode active material, comprising the following steps: (1) A process of mixing a positive electrode agent containing a positive electrode active material with an activating agent containing one or more alkali metal compounds to obtain a mixture; (2) The process of heating the mixture at a temperature T℃ to obtain the heated mixture; (3) The process of heating the heated mixture at a temperature above (T+300)℃ to recover the heated positive electrode active material.

3. The manufacturing method according to claim 1, wherein, The process (3) includes: (3a) The step of contacting the heated mixture with a liquid containing water to obtain a slurry containing a solid component and a liquid component, and then separating the slurry into the solid component and the liquid component; and (3c) A process of recovering the heated positive electrode active material by heating the solid component at a temperature of (1.6×T) °C or higher.

4. The manufacturing method according to claim 2, wherein, The process (3) includes: (3a) The step of contacting the heated mixture with a liquid containing water to obtain a slurry containing a solid component and a liquid component, and then separating the slurry into the solid component and the liquid component; and (3c) A process of recovering the heated positive electrode active material by heating the solid component at a temperature above (T+300) °C.

5. The manufacturing method according to any one of claims 1 to 4, wherein, In the process (2), the temperature T is lower than the melting start temperature of the activating agent.

6. The manufacturing method according to any one of claims 1 to 4, wherein, The positive electrode active material contains lithium compounds.

7. The manufacturing method according to any one of claims 1 to 4, wherein, The positive electrode active material comprises a composite oxide containing at least one element selected from group 1 and at least one element selected from group 2: Group 1: Ni, Co, Mn, Fe, Al, and P; Group 2: Li, Na, K, Ca, Sr, Ba, and Mg.

8. The manufacturing method according to any one of claims 1 to 4, wherein, The activating agent comprises at least one compound selected from potassium compounds and sodium compounds.

Citation Information

Patent Citations

  • Method for recovering active material from discarded battery material

    JP2012186150A